Thymus citriodorus as a source of antioxidants - Pereira, Olívia R. (2011)
Thymus species are well known as medicinal plants because of their biological and pharmacological properties, which include anti-asthmatic, anti-septic, antimicrobial and antioxidant. It is believed that part of these beneficial effects are due to the volatile constituents of Thymus, and thus, their essential oil composition has been the focus of many investigations. In contrast, there is only a limited number of data on the composition of other bioactive phytochemicals of Thymus and their potential biological effects. The present study aims to elucidate the phenolic composition of an ethanolic extract of Thymus citriodorus, as well as to determine its antioxidant capacity. The ethanolic extract was obtained by solubilisation of the defatted-dried plant with aqueous ethanol (80%) for twenty minutes, in a total number of five extractions. The total phenolic compounds in the extract accounted for 139±14 mg/g, as expressed as gallic acid equivalents. Further analysis of the ethanolic extract by high performance liquid chromatography (HPLC) and electrospray mass spectrometry in the negative mode allowed to conclude that its main phenolic components were rosmarinic acid (14.0±0.8 μg/mg extract), luteolin-7-O-glucoside (11±2 μg/mg extract), an apigenin derivative (9±2 μg/mg extract), eriodictyol-O-glucoside (5.5±0.7 μg/mg extract) and naringenin-O-glucoside (1.6±0.1 μg/mg extract). Moreover, the ethanolic extract of Thymus citriodorus exhibited a high antioxidative capacity, with EC50 values of 0.32±0.05 mg/ml for the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging potential and EC50 values of 0.8±0.2 mg/ml for the reducing power. Overall, these results suggest that Thymus citriodorus can be a good source of natural antioxidants.